The Role of Arabic Language Teachers in Developing the Cognitive Survey Using the Apprenticeship Strategy among high School Students in Al-Jouf region - Al-Rabia, Hanan Wanees (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the role of Arabic language teachers in developing the cognitive survey using the apprenticeship strategy among high school students in the Al-Jouf region; through the teachers’ perspectives and the views of the students. To achieve the goals of the study, the descriptive approach was used, and the questionnaire was the study tool, and it was applied to a sample of (278) female teachers and (327) female students at the secondary stage. The results showed that the response of the teachers at the level of the overall tool got a total average (4.20 out of 5), i.e. an estimate of practice (very large), and at the level of fields, implementation got the highest average (4.51) with an estimate (very large), followed by planning with an average (4.46) with an estimate (very large), then the evaluation with an average (3.64) is rated (highly). As for the female students ’response, I obtained a total average (3.28 out of 5), i.e. an estimate of (medium) practice, and at the level of fields, planning got the highest average (3.41) with a (large) estimate, followed by the evaluation with an average (3.34) with an estimate (average), then implementation with an average (3.10) (Average). Based on the results, the researcher recommended that the female teachers search for developing the cognitive survey of female students through the cognitive discipline strategy, and enriching the content of the Arabic language curricula at the secondary stage with some activities and training that contribute to increasing the students ’motivation towards research, investigation and polling, and training the teachers to develop the cognitive survey of female students during Teaching the Arabic language course at the secondary level; By employing modern teaching strategies based on female students ’positivity, and also providing an interesting educational environment for female students that motivates them to search, discover, and be attracted to every motive.